Critical Thinking in an EFL Research Writing Subject: An Analysis of Students’ Experience - Dwi Rahayu (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This research aims to find out EFL research writing students’ perception and challenges in implementing critical thinking activities. The subject English for Research Writing (ERW) in an an Foreign Language (EFL) subject aims to train students to conduct a small research and write the research report based on the United Nations’ Sustainable Development Goals (SDGs). This qualitative research underlies the concept based on the model of critical thinking from Bloom’s taxonomy and Paul and Elder Wheels of Reasons. Surveys to 97 respondents from three classes were conducted to collect the data. The results found that 79.4% respondents help them specify problems and solutions and 70% thought they could practice how to think critically. The challenges they faced (53%) was on the lack of English vocabulary, 38% found it hard to get ideas and 57% respondents found it hard to explain their opinion. The findings contribute to a clearer understanding on what aspects need to prepare and reflect on.